INFLUENCE OF BLOOD PLASMA MINERALS DURING ESTRUS ON CONCEPTION IN SAHIWAL CATTLE - AYAM, V B S; AWASTH, M K; TIWARI, R P; BHONSLE, D; GENDLY, M K (The Indian Journal of Animal Reproduction, 2015)
The present study was conducted to examine the influence of plasma levels of some macro-minerals and essential trace elements on conception in Sahiwal cattle. Blood plasma samples were collected from estrus cows (n=40) to estimate levels of macro-minerals viz. calcium, inorganic phosphorus and magnesium; and some essential trace elements viz. copper, cobalt, iron and zinc. Animals were inseminated 12 h after onset of estrus with good quality frozen semen. Significant differences (p<0.05) recorded in blood plasma calcium, inorganic phosphorus and magnesium between animals of conceived and non-conceived group suugested their association with conception failure in Sahiwal cattle.